2020
DOI: 10.1177/1729881420921676
|View full text |Cite
|
Sign up to set email alerts
|

A novel image edge smoothing method based on convolutional neural network

Abstract: In the field of visual perception, the edges of images tend to be rich in effective visual stimuli, which contribute to the neural network’s understanding of various scenes. Image smoothing is an image processing method used to highlight the wide area, low-frequency components, main part of the image or to suppress image noise and high-frequency interference components, which could make the image’s brightness smooth and gradual, reduce the abrupt gradient, and improve the image quality. At present, there are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hui-hong Xu et al have proposed to resolve the problem of edge detection and information capture better, significantly improves the edge effect and defend the efficiency of edge information. It reduces the signal-to-noise ratio of the smoothed image and greatly develops the effect of image smoothing [1]. Zhen Zheng et al haveproposed a novel image edge detection algorithm based on the gray prediction model.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hui-hong Xu et al have proposed to resolve the problem of edge detection and information capture better, significantly improves the edge effect and defend the efficiency of edge information. It reduces the signal-to-noise ratio of the smoothed image and greatly develops the effect of image smoothing [1]. Zhen Zheng et al haveproposed a novel image edge detection algorithm based on the gray prediction model.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Advanced DL techniques, including convolutional long shortterm memory [35], convolutional neural networks (CNNs) [36,37], generative adversarial networks (GANs), and conditional GAN (CGAN) [38][39][40][41][42][43][44], have been utilized in a number of satellite remote sensing researches [45][46][47][48]. These techniques have exhibited beneficial results in overcoming the limitations of conventional approaches relying on satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies utilizing satellite data have demonstrated the effectiveness of the ML and DL methods [19]. The state-of-theart DL techniques, such as convolutional neural networks (CNN) [20,21], convolutional long short-term memory [22], and conditional generative adversarial networks (cGAN) [23][24][25][26][27][28][29], have been used in various satellite remote sensing studies [30][31][32][33]. DL techniques have shown to overcome the limitations of traditional approaches of satellite observations.…”
mentioning
confidence: 99%